The Influence of Social Media Capability, Promotional Strategies, and Product Characteristics on Customer Interest and Product-Market Fit - Rahmadhani, May Vitha; Darlin, Evalina; Damiyana, Damdam; El Ikhsan, Nur; Zulfikr, Ali (International Journal of Business, Law, and Education, 2025)
This study investigates the influence of social media capability, promotional strategies, and product characteristics on customer interest and product-market fit. In today’s digital era, businesses face increasing pressure to utilize social media and effective marketing strategies while maintaining high product standards to meet customer expectations. A quantitative approach was employed using a structured questionnaire distributed to 200 respondents, with the data analyzed through SPSS version 25. Reliability and validity tests were conducted to ensure the robustness of the instrument. Multiple linear regression analysis was used to examine the relationship between the independent variables (social media capability, promotional strategies, and product characteristics) and the dependent variables (customer interest and product-market fit). The results revealed that all three independent variables had a significant and positive impact on customer interest and product-market fit. These findings suggest that businesses can enhance their market performance by strategically improving their digital presence, designing effective promotional campaigns, and offering products that align with customer preferences. The study provides valuable implications for marketers and product managers in developing integrated marketing and product strategies in highly competitive markets. Keywords: Social Media Capability, Promotional Strategies, Product Characteristics, Customer Interest, Product-Market Fit